“Native and indued Unto that element”: A material feminist approach to Ophelia’s death in William Shakespeare’s Hamlet - Bardaş, Gizem; Gülter, Isıl Şahin (My University, 2023)
The purpose of this paper is to bring the material, specifically the materiality of the human body and the natural world, to the forefront within the context of material feminist theory and practices in William Shakespeare’s renowned play Hamlet. Drawing on material feminist literary criticism as the principle guiding paradigm, this paper explores the manner in which Ophelia’s entanglement with the material world in Hamlet offers fresh insights into the reconsideration of many dichotomous categorizations, including culture/nature, man/woman, and human/nonhuman. In this regard, this paper, which draws mainly upon material feminisms’ notions of “trans-corporeality,” “diffraction apparatus,” and “thing power,” considers the materiality of the bodies an active force, Thus, this paper provides a critical perspective on Shakespeare’s conventional representation of Ophelia’s death. By paying particular attention to Ophelia’s entanglement with the natural world in Hamlet, this paper indicates that the reconceptualization of Ophelia’s entanglement with water in her drowning scene within the context of material feminist theory can offer a sense of fluidity, mobility, and dynamism between dichotomous categorizations.
Keywords: Beşeri Bilimler; Edebiyat; Kadın Araştırmaları